HUBUNGAN PERILAKU IBU DALAM MASASE DENGAN DURASI TIDUR BAYI USIA 3-6 BULAN DI BPM EKA KELURAHAN MEDAN DENAI 2021 - Debora Paninsari; Puti Lestari; Endang Herdiyanti; Gelora Pertiwi; Erika Fatrecia; Esmeralda . (STIKes Santa Elisabeth Medan, 2021)
Background: Massage is an old therapy that is known to many people and is the most sought after by mothers. Baby massage is very helpful for the physical and muscle development of the baby, it can also strengthen the relationship between mother and baby. The ability to lift the head when going to the stomach. Touching or massaging the baby after birth can provide a guarantee of body contact for the parents. Developmental factors in the learning process of the Little Psychic P can strengthen the growth of P and P development is very perfect. Methods: The type of research used was a Psurvey Panalytical approach with a cross-sectional approach. The research was carried out starting on P6 November P2021. Psample P35 respondents using the Ptotal Psampling technique. Results: Based on the Phasil, the majority of P13 respondents had sufficient knowledge, P7 (53.8%). Positive Attitude, with a normal P15 P(75.0%) incidence of sleep duration. Based on the Praise Pstatistic P that has been carried out, it shows the PP value = 0.04. The majority of P from P20 respondents, while P from P15 respondents had a P-negative attitude with the incidence of Pnormal sleep duration P as much as P5 P (33.3%) can be obtained P result P = 0.034. The majority of the 20 respondents who took the action were carried out, with the incidence of normal sleep duration being 15 (75.0%), while of the 15 respondents not doing it, with the incidence of normal infant sleep duration being 5 (33.3%). Can be obtained results P = 0.034 Conclusion : Touch therapy, especially massage produces beneficial physiological changes that can be measured scientifically, one of the benefits of infant massage is to increase sleep duration.